Bellagio STAMP: Principles for sustainability assessment and measurement - Pintér, László; Hardi, Peter; Martinuzzi, André; Hall, Jon (Ecological indicators, 2012)
► Revisiting how we assess progress is a key lever for sustainable development. ► High level principles can help guide measurement and assessment system design. ► BellagioSTAMP introduces eight high level principles. ► The principles cover both the content and process of measurement and assessment. Revisiting the way society defines and measures progress has been identified as one of the key levers in tackling the root causes of unsustainable development. The recent economic and food crises exposed a critical weakness in the ability of currently mainstream indicators of progress to provide early warning and take adequate preventive action. Since the early 1990s a growing number of organizations have been involved in the development of indicator systems around the key socio-economic and environmental concerns of sustainable development within their own context. In order to provide guidance and promote best practice, in 1997 a global group of leading measurement and assessment experts developed the Bellagio Principles. The Bellagio Principles have become a widely quoted reference point for measuring sustainable development, but new developments in policy, science, civil society and technology have made their update necessary. The Bellagio Sustainability Assessment and Measurement Principles (BellagioSTAMP) have been developed through a similar expert group process, using the original Principles as a starting point. Intended to be used as a complete set, the new BellagioSTAMP includes eight principles: (1) Guiding vision; (2) Essential considerations; (3) Adequate scope; (4) Framework and indicators; (5) Transparency; (6) Effective communications; (7) Broad participation; and (8) Continuity and capacity. The paper provides the rationale for the revision of the principles, their detailed description and guidance for their application.